LES of Normally Impinging Elliptic Air-Jet Heat Transfer at Re=4400 (Advances in Applied Mathematics and Mechanics, 2018)
Jet impingement induced heat transfer is an important issue in engineeringscience. This paper presents results of large eddy simulation (LES) of normally impingingelliptic air-jet heat transfer at a Reynolds number of 4400, with orifice-to-platedistance fixed to be 5 in the unit of jet nozzle effective diameter $D (=√ab)$. The ellipticaspect ratio ($a/b$) is 3/2. While the target wall is heated under some condition ofconstant heat flux. The LES are carried out using dynamic subgrid model and Open-FOAM.The distributions of mean velocity components, velocity fluctuations, and subgridstresses in vertical and radial directions, and the Nusselt numbers involving heattransfer through the target wall are discussed. The comparison with existing experimentaland numerical results shows good agreement.